OPPORTUNITIES OF THE DEVELOPMENT OF VALUES IN THE INTEREST-RELATED EDUCATION OF ADOLESCENTS - Pavlovs, Māris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Many schools and different educational institutions offer a wide range of out-of-class activities that promote the development of adolescents for a world in which people need to collaborate, to trust each other, to respect other people, different views and traditions. These activities deepen the knowledge acquired in the class in different school subjects, music, art, the use of modern technologies and in other fields. Interest-related education (out-of-class) activities support school teachers and parents in the process of the development of skills, abilities and personal traits, values for life. The task of any teacher in schools and out-of-school activities is to integrate the development of values in their daily activities. The teachers become the managers of the process of the development of values. A small-scale research was carried out with the aim to learn the priority values of teachers working in interest related education and the opportunities of interest-related education in the development of values of adolescents. The questionnaires were used to reach the aim of the research.